A medical information system to manage a cancer database - Ferrizzi, André Cid [UNESP]; Jardini, Toni [UNESP]; Costa, Leandro Rincon [UNESP]; Colombo, Jucimara [UNESP]; Rahal, Paula [UNESP]; Valêncio, Carlos Roberto [UNESP]; Mauad, Edmundo Carvalho; Kerr, Lígia Maria; Hidalgo, Geraldo Santiago (My University, 2008)
Cancer is the second main cause of death in Brazil, and according to statistics disclosed by INCA - National Cancer Institute 466,730 new cases of the disease are forecast for 2008. The storage and analysis of tumour tissues of various types and patients' clinical data, genetic profiles, characteristics of diseases and epidemiological data may provide more precise diagnoses, providing more effective treatments with higher chances for the cure of cancer. In this paper we present a Web system with a client-server architecture, which manages a relational database containing all information relating to the tumour tissue and their location in freezers, patients, medical forms, physicians, users, and others. Furthermore, it is also discussed the software engineering used to developing the system.
Keywords: Bioinformatics; Cancer database; Medical information system; Client-server architectures; Clinical data; Medical forms; National Cancer Institute; Relational Database; Tumour tissue; Web system; Client server computer systems; Computer software; Database systems; Information systems; Tumors